2018
DOI: 10.1590/1413-81232018234.17422016
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao baixo peso em idosos comunitários de sete cidades brasileiras: Estudo FIBRA

Abstract: The aim of this study was to assess the prevalence of being underweight among the elderly according to demographic and socioeconomic characteristics, health-related behaviors, diseases and health status. This was a cross-sectional multi-center study with 3,478 community-dwelling elders (≥ 65 years). The dependent variable was the prevalence of being underweight, classified by Body Mass Index < 22kg/m2. Adjusted prevalence rate ratios were estimated using multivariable Poisson regression. The mean age was 72.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
(28 reference statements)
2
5
0
11
Order By: Relevance
“…Hypertension was less prevalent among underweight older adults in the present study, which is in agreement with data reported in a previous study 7 . Ageing is accompanied by changes in vascular properties, such as hardening of the arteries, which plays an important role in the onset and progression of arterial hypertension 33 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Hypertension was less prevalent among underweight older adults in the present study, which is in agreement with data reported in a previous study 7 . Ageing is accompanied by changes in vascular properties, such as hardening of the arteries, which plays an important role in the onset and progression of arterial hypertension 33 .…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, underweight was more prevalent among smokers, which is in agreement with data found in the literature 7,19,20 . Analyzing 1954 individuals aged 60 years or older in four areas of the state of São Paulo, Zaitune et al 19 found a 90% higher prevalence rate of underwei- ght among smokers.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…O envelhecimento é caracterizado pelo declínio de diversas funções orgânicas, influenciando na capacidade de manutenção da homeostase e acarretando na maior suscetibilidade a doenças. 1 No que diz respeito às alterações orgânicas, há alterações digestivas, ocasionando na baixa ingestão calórica e protéica e na consequente desnutrição. Há alterações endócrinas, diminuindo a reposição de GH, IGF-1, PTH, testosterona e estrógeno, que interferem na lipólise, síntese de proteínas, na modulação muscular, na quantidade de células satélites e na liberação de citocinas, respectivamente.…”
Section: Introductionunclassified
“…6 Uma vez que o processo de envelhecimento implica em alterações absortivas do TGI e na depleção de fibras musculares, o idoso mau nutrido e com baixo peso está sujeito a potencialização destes processos. 1 Estes fatores podem levar ao maior risco de morbimortalidade por quedas e fraturas. 7 A presente revisão objetivou verificar o impacto da prática de exercício físico em idosos com baixo peso e sarcopenia, visto que este último é um componente frequentemente associado à magreza na população idosa.…”
Section: Introductionunclassified